Foreign Banks in Emerging Market Crises : Evidence From Malaysia - Detragiache, Enrica (IMF Working Papers; Working Paper ;, 2004)
Foreign banks have greatly increased their presence in emerging market countries in recent years. This paper compares the performance of domestic banks and a long-established group of foreign banks during the recent crisis in Malaysia. We find that the sharpest differences are between banks mainly active in Asia (including all domestic and some foreign banks) and foreign banks not specialized in Asia. The latter group performed better than the rest during the crisis, maintaining higher profitability thanks to higher interest margins and lower nonperforming loans. Foreign banks did not abandon the local market during the crisis and received less government support than domestic institutions.